P53-Related Anticancer Activities of Drimia calcarata Bulb Extracts Against Lung Cancer - Laka, K.; Mbita, Z. (Frontiers in Molecular Biosciences, 2022)
Current treatment strategies of lung cancer are ineffective, and lung cancer cases continue to rise; thus, novel anticancer drugs and targets are needed, and medicinal plants are promising to offer better alternatives. This study was aimed at analysing two p53 splice variants during the potential anticancer activities of Drimia calcarata methanol and water extracts against different human lung cancer cell lines of varying p53 mutation status, and these included mutant H1573 and mutant H1437 and p53-wild type (A549) cells. The anticancer activities were assessed by establishing the cytotoxic effect and the apoptosis-inducing capacity of these extracts, using the MTT assay and Annexin V analysis and fluorescence microscopy, respectively. The molecular mechanisms induced by these extracts were further evaluated using cell cycle analysis and RT-PCR. Both extracts demonstrated safety against noncancerous lung MRC-5 fibroblasts and exhibited significant anticancer potency (P˂0.001) against the H1437 (IC50 values: 62.50 μg/mL ME and 125 μg/mL WE), H1573 (IC50 value: 125 μg/mL for both extracts) and A549 (IC50 value: 500 μg/mL ME). The water extract had no effect on the cell viability of A549 cells. Treated H1437 cells underwent p53-dependent apoptosis and S-phase cell cycle arrest while H1573 treated cells underwent p53-independed apoptosis and G0/G1 cell cycle arrest through regulation of p21 mRNA expression levels. The expression levels of STAT1, STAT3, STAT5A and STAT5B genes increased significantly (P˂0.001) following the treatment of H1573 cells with ME and WE. Treatment of H1437 cells with ME upregulated the STAT1, STAT3, STAT5A and STAT5B mRNAs. Our results indicate that the proliferative inhibitory effect of D. calcarata extracts on A549 and H1573 cells is correlated with the suppression of Bcl-2, STAT3 and STAT5B while that is not the case in H1437 cells. Thus, our results suggest that the dysregulation of anti-apoptotic molecules Bcl-2, STAT3, STAT5A and STAT5B in H1437 may play a role in cancer cell survival, which may subsequently contribute to the development of p53-mutated non-small human lung cancer. Our results indicate that D. calcarata gives promising results as an anticancer agent for human non-small lung cancer cell lines, irrespective of p53 status.